2018
DOI: 10.1016/j.theriogenology.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation and fertility responses for sows receiving once daily boar exposure after weaning and OvuGel® followed by a single fixed time post cervical artificial insemination

Abstract: Boar exposure is used to stimulate follicle development and estrus in sows after weaning and also to improve semen uptake and sperm transport with insemination. However, the need and value of boar exposure is uncertain when ovulation induction is used. These studies were designed to determine the effect of daily boar exposure after weaning when used with ovulation induction and fixed time post-cervical artificial insemination (PCAI). In experiment 1, sows were weaned into stalls and assigned to receive 3 min o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…At estrus, the follicles present can be heterogeneous in size, granulosa cell numbers, and estrogen (Hunter and Wiesak, 1990). Most ultrasound data identify large follicles averaging 7 to 8 mm at estrus (Nissen et al, 1997;Lucy et al, 2001;Knox et al, 2002), but these measures can also vary by parity (Ulguim et al, 2018) and among sows before ovulation (Soede et al, 1998). Soede et al (1992) counted all follicles >4 mm at estrus and observed counts were closely related to number of corpora lutea (CL).…”
Section: The Physiology Of the Follicular Phasementioning
confidence: 99%
“…At estrus, the follicles present can be heterogeneous in size, granulosa cell numbers, and estrogen (Hunter and Wiesak, 1990). Most ultrasound data identify large follicles averaging 7 to 8 mm at estrus (Nissen et al, 1997;Lucy et al, 2001;Knox et al, 2002), but these measures can also vary by parity (Ulguim et al, 2018) and among sows before ovulation (Soede et al, 1998). Soede et al (1992) counted all follicles >4 mm at estrus and observed counts were closely related to number of corpora lutea (CL).…”
Section: The Physiology Of the Follicular Phasementioning
confidence: 99%
“…In this regard, Driancourt et al [17] showed that weaned primiparous sows are less responsive than weaned multiparous sows to the GnRH agonist buserelin. It is also interesting to note that a substantial number of weaned sows with few parities had small ovarian follicles at weaning [23,31]. Sows had shown clear individual differences in average follicular size at weaning [23] and even also by the third day after weaning [32].…”
Section: Discussionmentioning
confidence: 99%
“…Successful insemination of gilts depends primarily on the ovulation and inseminationtime [30] . In theory, sperm show optimal fertility at 24 hours after insemination [31,32] . However, if insemination is done too late, the oocytes would be degraded [33] , which negatively impacts the sow fertility, including reductions in pregnancies, fertilization rates [34] , and embryo survival [35] .…”
Section: Discussionmentioning
confidence: 99%